A comparison of social accounting between local public healthcare services: An empirical research (Italian Journal of Public Health, 2010)
Introduction: Social accounting in healthcare is a quantitative–qualitative accounting tool which marks thebond between the business and its social background. It displays healthcare business results and informationto the stakeholder. Actually, its use is not widespread in Italy, but often published in United States and otherCountries.Methods: This work is based upon an empirical research, studying social accounting from Local Health Units(LHU, Italian ASL) of Adria, Brindisi, Firenze and Umbria region published between 2006 and 2008.These documents have been analyzed, studying the business’ structure, healthcare services, social andeconomical conditions, financial status, performance indexes and much more data about most companyactivities.Results: Accountability in Italy has been studied carefully through longitudinal and cross-sectional analysis,observing models and contents, elaborating a concrete proposal for social accounting.Discussion: Social accounting in healthcare can guarantee important information for non-expert users andexpert technicians, allowing the former to take more conscious decisions, and the latter to study its businessaspects more deeply. This is made possible by the consideration of extended economical data available inother accountability forms (like annual financial statement), and other performance indexes which givevaluable data about social impact, efficiency and effectiveness to the end user.
Keywords: social accounting; social audit; accountability; health communication